Evaluation of Two Methods for Determination of CD64 as a Diagnostic Marker of Infection in Critically Ill Adults. (20th December 2016) - Zinsly Sampaio Camargo, Thiago; Marra, Alexandre R.; Bacal, Nydia Strachman; Casaroto, Eduardo; Pinto, Lilian Moreira; Pasternak, Jacyr; Victor, Elivane da Silva; dos Santos, Oscar Fernando Pavão; Edmond, Michael B.
Abstract : Objectives . Diagnostic markers of infection have had little innovation over the last few decades. CD64, a marker expressed on the surface of neutrophils, may have utility for this purpose. Methods . This study was conducted in an adult intensive care unit (ICU) in São Paulo, Brazil, with 89 patients. We evaluated CD64 in patients with documented or clinically diagnosed infection (infection group) and controls (patients without any evidence of infection) by two different methodologies: method #1, an in house assay, and method #2, the commercial kit Leuko64 (Trillium Diagnostics). Results . CD64 displayed good discriminating power with a 91.2% sensitivity (95% CI 90.7–91.6%) for detecting infection. The commercial kit (Leuko64) demonstrated higher specificity (87.3%) compared with method #1 as well as better accuracy (88.8%). Conclusions . CD64 seems to be a promising marker of infection in the intensive care setting, with Leuko64 showing a slight advantage.